Cystic Endometrial Hyperplasia Complex (CECH)- Stump pyometra a literature review - Hobold, Carolini; Cardoso, Ewerton; Souza, Flávia Coelho de; Tonon, Laura Veira; Rychesck, Mateus; Warmiling, Bruna (Seven Editora, 2023)
Cystic endometrial hyperplasia complex (CHEC) is an exaggerated response of the uterine endometrium to chronic progesteronic stimulation, resulting in the accumulation of exudate in the uterine lumen. The inflammatory process, which occurs in the uterus, is described as an exacerbated reaction of the endometrium to the repeated release of progesterone, caused by high levels of estrogen, which is responsible for maintaining cervical relaxation for longer in the luteal phase, resulting in the accumulation of fluids in the glands or in the uterine cavity. Stump pyometra occurs similar to classic pyometra, but is triggered by Remnant Ovary Syndrome (ORS), that is, the total non-removal of ovarian tissues. The retained ovarian tissue can implant in the abdominal cavity and vascularize, thus maintaining its functionality and secretion of estrogen and progesterone. Such production can occur cyclically, stimulating the remaining endometrium, leading to the accumulation of fluids within the stump and predisposing the female to a diestrus infection. The presence of progesterone can also be from drugs that have progesterone as a source, such drugs are used to treat dermatitis and urinary incontinence. Conclusion. The treatment established must be immediate and precise since the condition in the most severe cases can develop endotoxemia or sepsis at any time. DOI:https://doi.org/10.56238/sevened2023.004-056